حق الاضراب وآثاره على المرافق العامة في التشريع الجزائري - غريسي, العيد; ميموني, عبد الحليم (unuversity of eloued- جامعة الوادي, 2018)
يتناول هذا البحث محورين هامين في مجالات القانون هما محور الحقوق والحريات الأساسية، والمتمثلة في حق العمال والموظفين في ممارسة حق الإضراب، ويقابله المحور الثاني والمتمثل في أهمية المرافق العامة في تحقيق حاجاتهم ومطالبهم، وهذه المرافق تقوم على مبادئ أساسية أهمها مبدأ سير المرافق العامة بإنتظام واضطراد، لكن ممارسة حق الإضراب يتعارض ويصطدم مع هذا المبدأ، وتنتج آثار ذات حده وجسامة خطيرة، أما في الجزائر فقد تمت ولادة الإضراب بعد فترة عصيبة عاشها الموظفون زامنت تطورات سياسية هامة شهدتها البلاد، صارعت خلالها فئتي العمال والموظفين تعنت الدولة وسلطتها لتستحق بكل جدارة هذا الوسام بصدور دستور سنة 1989 الذي اعترف بحق الإضراب في القطاعين العام والخاص، وتأكيدا لهذا الاتجاه أصدر المشرع القانون رقم 90/02 المعدل والمتمم بالقانون رقم 91/27 المتعلق بالوقاية من النزاعات الجماعية في العمل وتسويتها وممارسة حق الإضراب. ولقد تطرقنا في هذا البحث الى الكيفية أو المنهج الذي اعتمده المشرع الجزائري في تحديد شروط وكيفيات ممارسة حق الإضراب للتقليل من حدة الآثار الخطيرة التي يخلفها على سير المرافق العامة.This research deals with two important axes in the fields of law, namely the center of fundamental rights and freedoms, represented by the right of workers and employees to exercise the right to strike. The second axis is related to the importance of public utilities in achieving their needs and demands. These facilities are based on basic principles, , But the exercise of the right to strike conflicts with this principle and produces effects of severe severity and gravity. In Algeria, the strike was born after a difficult period experienced by the staff, which ensured important political developments in the country. In this regard, the legislator issued Law No. 90/02, amended and supplemented by Law No. 91/27 on prevention of the right to strike in the public and private sectors. Collective labor disputes, settlement and exercise of the right to strike. In this paper, we discussed the method or method adopted by the Algerian legislator in determining the conditions and modalities of exercising the right to strike in order to minimize the serious effects it imposes on the functioning of public facilities.
The right to strike and it's impact on public services in Algerian law
مقال
Keywords: حق الاضراب، المرافق العامة، الموظف العمومي، التشريع الجزائري.: Right of strike, public utilities, public official, Algerian legislation